From Scratch to Success: The growth of organic food company. - Shivani Kalra, Dr. Shailja Dixit, Dr. Bobby W. Lyall (Drugs and Cell Therapies in Hematology, 2021)
The company that started from Lucknow, a city in Uttar Pradesh has marked its presence in more than 40 countries world-wide. Stared with a noble cause to promote healthy living, the company aims at earning Rs. 500 Cr by the end of the year 2020. Started by a US based couple in search of spiritual path in India, Organic India has emerged as a brand that promotes love, loyalty, genuineness and healthy lifestyle. This case, studies the hurdles faced by a startup company in India and finally emerged as a global leader by exporting organic food in more than 40 countries.